Epidermal growth factor receptor inhibition for the treatment of glioblastoma multiforme and other malignant brain tumours - Halatsch, Marc-Eric; Schmidt, Ursula; Behnke-Mursch, Julianne; Unterberg, Andreas; Wirtz, Christian Rainer (Cancer treatment reviews, 2006)
Gliomas are the most common primary central nervous system tumours and about 55% are glioblastoma multiforme (GBM). Between 40% and 50% of GBM have dysregulated epidermal growth factor receptor (HER1/EGFR), and almost half of these co-express the mutant receptor subtype EGFRvIII, which may contribute to the aggressive and refractory course of GBM. Limited therapeutic options exist for GBM, and recurrence is common. Standard therapy is surgical resection, where possible, and radiotherapy. Adjuvant chemotherapy provides a modest survival benefit. New therapies are essential, and HER1/EGFR-targeted agents may provide a viable strategy. The HER1/EGFR tyrosine kinase inhibitors erlotinib and gefitinib are in advanced clinical development for glioma, and a number of trials are in progress, or have recently been completed. Preliminary results with gefitinib show no objective responses, but do provide evidence of disease control. In contrast, preliminary data with erlotinib appear more encouraging. Erlotinib inhibits wild-type HER1/EGFR and EGFRvIII, which may underlie its promising clinical activity. Other HER1/EGFR-targeted agents are also being investigated for glioma, including monoclonal antibodies, radio-immuno conjugates, ligand-toxin conjugates, antisense oligonucleotides and ribozymes. Further studies will define their clinical potential and hopefully provide new, effective treatments for GBM and other malignant brain tumours.
Gesehen am 05.05.2021